“El rostro de los días”: sobre la corporalidad y las almas entre los mayas k’iche’ de Santiago Momostenango - Alonso Zamora Corona (Journal de la Société des Américanistes)
The study of ideas regarding corporeality and souls has consolidated itself in recent years as one of the most important subjects in our knowledge of the Maya peoples of the past and the present (Pitarch 1996, 2011; Figuerola Pujol 2010; Velásquez García 2015). Regarding the K’iche’ Maya of Santiago Momostenango, important works have been dedicated to subjects such as calendric practices (Tedlock 1992), cosmology (Cook 1981) and ethnohistory (Carmack 1995), but information regarding the body and souls is still unsystematic. In this article, I present new information regarding the body and the soul among the Momostecos, following the recent proposal of Pedro Pitarch regarding Maya personhood (2011). Notable is the existence among the momostecos of the chikop, a soul with the form of a bird very similar to the “bird of the heart” of the Maya Tzeltal, which can be punished by the ancestral deities when people forget to do offerings at their patrilineage’s altars.